2015
DOI: 10.1002/pc.23395
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of successive alkali treated completely biodegradable short jute fiber reinforced PLA composites

Abstract: The natural fiber reinforced biodegradable polymer composites were prepared with short jute fiber as reinforcement in PLA (Poly lactic acid) matrix. The short jute fiber is successively treated with NaOH at various concentrations (5%, 10%, and 15%) and H 2 O 2 . The composites were prepared with untreated and treated short jute fibers at different weight proportions (up to 25%) in PLA and investigated for mechanical properties. The results showed that the composite with successive alkali treated jute fiber at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…For this reason, the tensile modulus of PLA/DHF biocomposite increases due to addition of DHF. Moreover, Gunti et al [17] also agreed that the modulus of biocomposite is highly depending on the amount of filler. Hence, the biocomposite with higher fiber content showed higher tensile modulus.…”
Section: Tensile Propertiesmentioning
confidence: 93%
“…For this reason, the tensile modulus of PLA/DHF biocomposite increases due to addition of DHF. Moreover, Gunti et al [17] also agreed that the modulus of biocomposite is highly depending on the amount of filler. Hence, the biocomposite with higher fiber content showed higher tensile modulus.…”
Section: Tensile Propertiesmentioning
confidence: 93%
“…The authors found that the incorporation of fibers treated by 5% alkalization did not produce a significant increase in strength; in turn, the highest increase in strength of the material reinforced with 25% jute fibers occurred with the incorporation containing 10% of fibers treated with NaOH. However, this modification corresponded to rises of only 7.7% and 8.0% in tensile and flexural strengths, respectively [26,27]. Figure 8 shows SEM images including fiber fragments that evidence breaking, suggesting an efficient load transfer from the matrix to the reinforcement in comparison with the transfer to untreated fibers, as shown in Figure 7.…”
Section: Macromechanical Properties (Tensile)mentioning
confidence: 98%
“…Sisal fiber (SF), with a range of advantages such as low cost, low density, high specific strength and specific modulus, no health risk, has been a promising reinforcement for use in WPCs . Xie et al .…”
Section: Introductionmentioning
confidence: 99%